ROAD BOUNDARY DETECTION USING SEGMENTATION ON STEREO IMAGES - T. Son, T.; Takeuchi, A.; Mita, S. (Vietnam Journal of Science and Technology, 2012)
ABSTRACTIn this paper, a road detection method based on an  image segmentation and stereo vision ispresented. Road detection process is a key issue for an autonomous driving system in urbanenvironment. Image-based road detection algorithm is applied on sources of visual informationrecorded by stereo cameras when our car is running  on road. Our method combines a posterioriprobability and visual information for image segmentation. The depth map in stereo camera iscalculated on real time by a circuit board and it is utilized to rectify the boundary on left andright side of road. The method is composed of threesteps. Firstly, a road identifier is trainedwith supervised learning algorithm. Secondly, road  regions are detected by combining aposteriori probability and visual information usingimage segmentation algorithm. In the laststep, the segmentation result is combined with the  depth-map image to correct the boundary. Experimental results are presented for video sequences of road in urban areas.Keywords.SWA algorithm, Bayes's rule, depth map, road detection.